Antioxidant Activity of Arctium lappa L. and Its Effect on Biochemical Parameters in Exercised Rats - Horng, Chi-Ting; Tsai, Ming-Ling; Hsueh, Chao-Wen; Hsu, Shun-Yuan; Wang, Hui-Yun; Chen, Fu-An (Asian Journal of Chemistry, 2012)
The root of the medicinal plant locally known as burdock (Arctium lappa L.) has long been cultivated as a popular vegetable across Taiwan for human consumption and traditional medicine. The present study is to investigate the antioxidant activity of Arctium lappa and its effect on biochemical parameters in exercised rats. The extract of root of burdock was prepared and then subjected to analysis of polyphenols and 2,2-diphenyl-1-picrylhydrazyl (DPPH) free radical scavenging activity. Sprague-Dawley rats were divided into five groups including control (fed with drinking water) and three groups of different doses of burdock extracts (BE). After eight weeks, an exhaustive exercise test on a treadmill and the measurement of biochemical parameters related to fatigue were carried out. The results revealed that burdock extract was able to extend significantly the endurance time of treadmill running to exhaustion, as well as decreasing the blood lactate and serum urea nitrogen contents with comparison to that of control group. Malondialdehyde level of rats in burdock extract treated groups were significantly decreased, while superoxide dilmutase (SOD) were significantly increased compared with that of control group. The results shows that Arctium lappa is capable of ameliorating biochemical parameters related to fatigue in the exercised rat model that could be associated with the antioxidant polyphenols with free radical scavenging activities.